Invasive pneumococcal disease caused by non-vaccine Streptococcus pneumoniae serotype 24B in an immunocompetent child - Naotaka Tamai, MD; Masayoshi Shinjoh, MD, PhD; Hiroyuki Oikawa, MD; Riku Hamada, MD; Tomohiro Morio, MD, PhD; Goro Koinuma, MD; Takao Takahashi, MD, PhD (Radiology Case Reports, 2024)
Invasive pneumococcal disease typically occurs in immunocompromised patients, although some vaccine strains of Streptococcus pneumoniae have been reported to cause invasive pneumococcal disease in immunocompetent vaccine recipients. In this study, we presented a case of a 16-month-old immunocompetent patient with lung abscess and empyema caused by nonvaccine S. pneumoniae serotype 24B. A consolidation occupying the right upper lobe in the chest computed tomography results, as observed at presentation, changed to thick-walled cavitary lesions at the end of a month of intravenous antibiotics, and antibiotics were continued for a total of two months. To the best of our knowledge this is the first report that focuses on the risk of invasive pneumococcal disease caused by S. pneumoniae serotype 24B in an immunocompetent child.